2021
DOI: 10.3389/fpain.2021.728045
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Dependent Electrical Stimulation of PFC and ACC for Acute Pain Treatment in Rats

Abstract: As pain consists of both sensory and affective components, its management by pharmaceutical agents remains difficult. Alternative forms of neuromodulation, such as electrical stimulation, have been studied in recent years as potential pain treatment options. Although electrical stimulation of the brain has shown promise, more research into stimulation frequency and targets is required to support its clinical applications. Here, we studied the effect that stimulation frequency has on pain modulation in the pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 73 publications
(100 reference statements)
0
9
0
Order By: Relevance
“…Currently, the mechanisms underlying pulpitis-induced pain were primarily at the peripheral level, with limited research on central mechanisms. , , While it is known that ACC was activated during pain, ,, its involvement in pulpitis-induced pain remained unclear. To address these gaps, we conducted transcriptomic and proteomic analyses and verified the key DEGs and DEPs by qRT-PCR in the ACC of pulpitis models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the mechanisms underlying pulpitis-induced pain were primarily at the peripheral level, with limited research on central mechanisms. , , While it is known that ACC was activated during pain, ,, its involvement in pulpitis-induced pain remained unclear. To address these gaps, we conducted transcriptomic and proteomic analyses and verified the key DEGs and DEPs by qRT-PCR in the ACC of pulpitis models.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, ACC plays an important role in pain sensation and pain-related affective emotions. Neurons in ACC were activated in acute and chronic pain. However, whether ACC is involved in pulpitis-induced pain remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other brain structures, the ACC opioid system is critical to selectively modulate the aversive quality of noxious mechanical stimulation in neuropathic pain models ( 97 ). In rodents, ACC high-frequency stimulation reduced aversive pain responses induced by mechanical nociceptive stimuli, while low-frequency stimulation increased pain aversive behaviors ( 98 ). Optogenetic or chemogenetic stimulation of the ACC reduced abdominal hyperalgesia and pain-related anxiety in a rat model of chronic pancreatitis ( 99 ).…”
Section: Preclinical Modelsmentioning
confidence: 99%
“…Activation of cortical fibers projecting from the somatosensory cortex I (S1) to the ACC enhance hyperalgesia and direct stimulation of the rACC also enhances the nociceptive response to colorectal distension (CRD) [ 9 ]. Further studies have observed that stimulation frequencies between 20 and 100 Hz delivered to the ACC can enhance aversive pain behavior and potentiate spinal excitatory transmission while higher frequency (120 Hz) stimulation was observed to reduce aversive pain in response to mechanical stimuli [ 10 , 11 ]. In addition, high-intensity electrical and chemical stimulation of metabotropic glutamate receptors (mGluRs) within the ACC produces a faciliatory effect on spinal nociception while also contributing to the formation of long-term contextual and auditory fear memory [ 12 , 13 ].…”
Section: Animal Studies Of Accmentioning
confidence: 99%